The Effectiveness of Legal Policies on Micro and Small Business Empowerment in Pandemic Time - Muhammad Ilyas; Rizki Ramadani (SASI, 2022)
Introduction: MSMEs made a significant contribution to the Indonesian economy at the beginning of 2018. However, since COVID-19 has become a global pandemic, micro, small, and medium-sized enterprises (MSMEs) have been heavily impacted, due to a series of social restriction policies enacted by the government. In order to resolve issues, the government must assist and empower the MSME sector so that it can survive the pandemic. However, not many studies have been carried out regarding the extent to which empowerment policies by local governments have been effective in the field.